Economic and Social Context of Decent Work in the Philippine Setting - Castro, Lina V. (Philippine Journal of Labor and Industrial Relations, 2021)
This paper attempts to capture the key characteristics of decent work within the context of economic and social aspects and their applicability in the Philippine setting. It tries to make more precise in operational terms through statistical indicators, the socio-economic aspects of decent work in the country. Statistical data are derived from various sources, in particular the National Statistics Office, National Statistical Coordination Board, International Labor Organization and the United Nations Development Programme, among others. Overall, the paper contributes to the debate on possible policies and programs that government, employers' and workers' organizations need to implement to make decent work a greater reality among the working population.